2022
DOI: 10.1111/ijac.14124
|View full text |Cite
|
Sign up to set email alerts
|

Dry sliding wear analysis of vacuum die‐casted hybrid aluminum nanocomposites using the DOE Taguchi method

Abstract: This study focuses on the impact of wear process parameters on the sliding wear behavior of titanium oxide (TiO 2 ) and yttrium oxide (Y 2 O 3 ) reinforced pure aluminum (Al) hybrid nanocomposites. The optimization of wear test parameters for hybrid aluminum matrix nanocomposites (HAMNCs) was examined with the design of experiments Taguchi method. The HAMNCs were manufactured by a vacuum die casting technique using a unique double-layer feeding method. Initially, mechanical characterization as tensile and hard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Generally, the Al 2 O 3 has high hardness and resists the indentation against the indentations 19 . Besides, the ceramic particle appearances in soft matrix recorded better hardness and resistance to abrasion 37 . The VHN of the S2 sample containing 3 wt% SiC nanoparticle is 78 ± .8HV and raised by 85 ± 1.7HV due to homogenous particle distribution, as evidenced in Figure 7.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Generally, the Al 2 O 3 has high hardness and resists the indentation against the indentations 19 . Besides, the ceramic particle appearances in soft matrix recorded better hardness and resistance to abrasion 37 . The VHN of the S2 sample containing 3 wt% SiC nanoparticle is 78 ± .8HV and raised by 85 ± 1.7HV due to homogenous particle distribution, as evidenced in Figure 7.…”
Section: Resultsmentioning
confidence: 94%
“…19 Besides, the ceramic particle appearances in soft matrix recorded better hardness and resistance to abrasion. 37 The VHN of the S2 sample containing 3 wt% SiC nanoparticle is 78 ± .8HV and raised by 85 ± 1.7HV due to homogenous particle distribution, as evidenced in Figure 7. While compared to cast AZ91D alloy, the VHN of S1, S2, S3, and S4 is improved by 9%, 13%, 23.18%, and 24.6%, respectively.…”
Section: Vickers Hardness Number (Vhn)mentioning
confidence: 88%
“…The vegetable oil had lubricating properties similar to conventional cutting fluid. Singh (2022) used Taguchi method to investigate dry sliding wear in aluminum nanocomposites. It was found that 5-wt% TiO2 + 5-wt% Y2O3 nanocomposite showed excellent tensile strength and micro hardness.…”
Section: Introductionmentioning
confidence: 99%